Managing service quality by managing the service customer - Krishna K. Govender (South African Journal of Business Management, 1998)
The need to manage service quality is becoming more urgent as links between service quality and business performance is becoming apparent. By breaking away from the traditional focus on the service employee, this article sheds light on strategies to manage service quality by managing the service customer. A survey was conducted among a sample of commercial bank customers to determine the effects of two types of socialization strategies on their perception of service quality. It was ascertained that by means of formal and informal socialization tactics, service firm managers could influence their customers' perception of the overall service quality as well as the employee service quality. Empirical evidence also supports the view that an organizational climate which supports service has a positive impact on the customers' perception of the employee service quality. The implications of these findings for service organization managers are discussed, and the opportunities for future research are also identified.
Keywords: 650